High levels of incidental physical activity are positively associated with cognition and EEG activity in aging - Sanchez-Lopez, Javier; Silva-Pereyra, Juan; Fernández, Thalía; Alatorre-Cruz, Graciela C.; Castro-Chavira, Susana A.; González-López, Mauricio; Sánchez-Moguel, Sergio M. (PLOS ONE, 2018)
High levels of physical activity seem to positively influence health and cognition across the lifespan. Several studies have found that aerobic exercise enhances cognition and likely prevents cognitive decline in the elderly. Nevertheless, the association of incidental physical activity (IPA) with health and cognition during aging has not been studied. Thus, the aim of this study was to evaluate the association of IPA level with cognitive functions and resting electroencephalogram (EEG) in healthy old participants. Participants (n = 97) with normal scores on psychometric and neuropsychological tests and normal values in blood analyses were included. A cluster analysis based on the scores of the Yale Physical Activity Scale (YPAS) allowed the formation of two groups: active, with high levels of IPA, and passive, with low levels of IPA. Eyes-closed resting EEG was recorded from the participants; the fast Fourier transform was used offline to calculate absolute power (AP), relative power (RP), and mean frequency (MF) measures. There were no differences in socioeconomic status, cognitive reserve, general cognitive status, or lipid and TSH profiles between the groups. The results of cognitive tests revealed significant differences in the performance variables of the WAIS scores (p = .015), with advantages for the active group. The resting EEG exhibited significantly slower activity involving the frontal, central, and temporal regions in the passive group (p < .05). Specifically, higher delta RP (F7, T3), lower delta MF (F4, C4, T4, T6, Fz, Cz), higher theta AP (C4), higher theta RP (F4, C4, T3, Fz), lower alpha AP (F3, F7, T3), lower alpha RP (F7), and lower total MF (F3, F7, T3, T5, Fz) were found. Altogether, these results suggest that IPA induces a neuroprotective effect, which is reflected both in behavioral and electrophysiological variables during aging.